A study on management of mangrove and the knowledge of local community in Bahoi of West Likupang Subdistrict of North Minahasa District - Vonne Lumenta; Stephanus V. Mandagi; Markus T. Lasut (Sam Ratulangi University, 2017)
A study on community based mangrove management was conducted in Bahoi of North Minahasa District of North Sulawesi Province of Indonesia. This aims of the study were to examine the management of mangrove including community involvement in the whole processes as well as the institutional settings; to examine knowledge and atitute of the community of Bahoi toward the management processes; to find out its impacts to the community and marine ecosystems. Methods used in this study were interviews and surveys. For the former, all key persons involving in the management including representative of government were interviewed. With the latter, 30 community members or around 10% of total population were randomly selected and requested to fill in questionnaries containing multiple choices questions to meet the objectives of the study. This study revealed that the management of mangrove has been projects driven activities since year 2000. Yet communities were partly involved in the management including during the establishment of organization and village Ordinance, the survey shows that only 30% of respondents actively involved. That is why 63% of respondent argue that the management processes is lacking and 23% recon that it should be improved. Moreover, 100% of respondents claim that they strongly support conservation of mangrove and other coastal resources; 90% of the respondent answer that cultural background (Sangiran ethnicity) drives their attitude about preserving the coastal resources. In terms of implication of the management mangrove and other coastal resources in Bahoi, they argue that it has resulted in improvement of income and a healthy mangrove ecosystem. Keywords: Mangrove, Management, Bahoi Abstract Penelitian ini tentang pengelolaan mangrove berbasis masyarakat telah dilakukan di Desa Bahoi di Kabupaten Minahasa Utara Propinsi Sulawesi Utara Indonesia. Tujuan penelitian ini untuk mengetahui proses dan dinamika pengelolaan mangrove berbasis masyarakat khususnya tentang keterlibatan masyarakat dan faktor-faktor yang mempengaruhi pengelolaan terutama pengetahuan dan sikap masyarakat, serta dampak pengelolaan terhadap masyarakat dan ekosistem pesisir lainnya. Teknik pengumpulan data yang digunakan adalah wawancara (interview) dan survei. Wawanara telah dilakukan terhadap semua tokoh kunci yang terlibat dan mempengaruhi pengelolaan, sedangkan untuk survei dengan menggunakan kuisioner, sejumlah 30 responden atau sekitar 10% dari jumlah penduduk telah dipilih secara random bersedia memberikan jawaban atas pertanyaan-pertanyaan pilihan berganda (multiple choises). Penelitian ini mengdapatkan bahwa pengelolaan mangrove di Desa Bahoi didorong oleh proyek pemerintah sejak tahun 2000. Namun masyarakat belum seluruhnya dalam proses pengelolaan mangrove termasuk dalam pembuatan lembaga dan Peraturan Desa tentang pengelolaan sumberdaya pesisir. Makanya 63% responden mengakui kalau pengelolaan yang ada kurang baik dan 23 % menyarankan perlu perbaikan. Selanjutnya 100% menyatakan mendukung sepenuhnya usaha konservasi mangrove dan sumberdaya pesisir lain. 90 % dari mereka percaya bahwa factor budaya Sangir yang mendorong sikap mereka untuk menjaga lingkungan pesisir. Mengenai dampak pengelolaan ekosistem mangrove, masyarakat dan pemerintah menjawab bahwa telah membantu meningkatkan pendapatan atau ekonomi masyarakat dan ekosistem mangrove semakin sehat. Kata kunci: Mangrove, Managemen, Bahoi